Effect of Fermented Tofu Industrial Wastewater and Coconut Water Enriched with Em4 on the Growth of Water Spinach (Ipomoea Reptans Poir) - Hidayatullah Az Zuhry, Syarif; Faqih, Achmad; Royyan, Royyan (Indonesian Journal of Multidisciplinary Science, 2025)
Tofu wastewater, a by-product of tofu production, can reach volumes up to ten times that of the processed soybeans. This waste contains organic compounds like proteins, carbohydrates, and fats, as well as essential minerals such as nitrogen, phosphorus, and potassium, which benefit plant growth but pose environmental risks if untreated. Fermenting this wastewater with the EM4 bioactivator and coconut water—rich in growth hormones and minerals—produces a nutrient-rich, eco-friendly liquid organic fertilizer (LOF). This fertilizer serves as an alternative to chemical fertilizers often misused by farmers. This study evaluates the use of fermented tofu wastewater and coconut water as LOF for growing land spinach (Ipomoea reptans), chosen for its high consumption and easy cultivation. Results show that applying this fermented mixture significantly affects growth parameters, including stem diameter, fresh weight, number of nodes, leaf area, plant height (at 21 and 28 days), and number of leaves (at 14, 21, and 28 days). The best growth was observed in treatment F6 (40% tofu wastewater fermentation), though it did not exceed the positive control. These findings suggest that fermented tofu wastewater and coconut water enriched with EM4 have potential as sustainable liquid organic fertilizers that promote plant growth while reducing tofu industry waste.